PERAN GENERASI MILENIAL TERHADAP PERKEMBANGAN FINTECH STUDI KASUS MAHASISWA PERBANKAN SYARIAH STAI AL-ISHLAHIYAH BINJAI - Hendra Hendra; Yanti Tri Auri; Rachmadita Ridha (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2022)
The rapid growth of technology has made all sectors influential, namely the education sector, industry, as well as the economic, financial and banking sectors. The link between the millennial generation and the development of fintech, one of which is because the millennial generation is a technology literate generation that is able to accept a financial technology innovation. The purpose of the study was to determine the extent of the role of the millennial generation in the development of fintech. This research was conducted on Islamic banking students at STAI Al-Ishlahiyah Binjai Stambuk 2016, and the data collection in this collection was through a qualitative descriptive method. This research method uses inductive, then analyzed and then presented in writing in the report, namely in the form of data found from interviews, and documentation. The results of research conducted with Islamic banking students STAI Al-Ishlahiyah Binjai regarding the role of the millennial generation in the development of fintech is very important, this is shown by the results of interviews that researchers have conducted, namely 7 out of 10 students have understood fintech and they participate in the development of fintech that which in this case they have played a role in the development of financial technology today, and the rest of them do not understand and are not interested in using fintech due to the lack of education and socialization about fintech.